The Role of Competitive Intelligence in Trade Facilitation in an Emerging Economy - Maune, Alexander (Journal of Economics and Behavioral Studies, 2018)
This article analyzed the role of competitive intelligence in trade facilitation in Zimbabwe, whose economy depends largely on exports of unprocessed minerals and tobacco among others to international markets. This study has been carried out when the country is facing persistent trade deficits as well as a number of trade complexities.This article was informed by both deductive and inductive approaches with an econometric model being developed to analyse the relationship between economic growth (GDP) and trade. A multiple regression analysis was used to measure this phenomenon using secondary data that was extracted from World Bank`s databases for the period 1975-2015. This analysis was then followed by a literature review of some identified peer-reviewed, published articles and documents that necessitated the development of a conceptual framework. The framework complemented the findings of the regression model.The special role of trade in economic development was analyzed using an econometric model with a positive correlation of 0.8045 obtained. An F-value equal to 34.86 was also obtained which is much greater than 1 thereby suggesting that the hypothesis H0 is false. This was also confirmed by the p-value of 0.000000002526< 0.05. The coefficient of determination R2, also known as the multiple R2, expresses the proportion of total variance explained by the independent variables and in this case an R2 of 0.647224 shows that the model was able to explain approximately 64.72% of the variation embedded in GDP. Competitive intelligence has been identified as a critical component in trade facilitation with positive effects on growth of trade, economy growth and development. It was also found that competitive intelligence enhances trade facilitation and hence its role cannot be overemphasized. This article is, however, of great significance to policy-makers, researchers and the academia.